2017
DOI: 10.1515/pomr-2017-0097
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Soil Settlement Prediction and Its Application In Large-Scale Marine Reclamation Artificial Island Project

Abstract: In an artificial island construction project based on the large-scale marine reclamation land, the soil settlement is a key

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…In the presented examples of automated interpretation of laboratory test results, selected possibilities of conducting numerical analyses with the use of MES have been demonstrated, which in their application are limited only by the imagination of experimenters (see numerical analyses based on the inclusion of soil microstructure, eg [22]).…”
Section: Examples Of Application Of Proposed Methodologymentioning
confidence: 99%
“…In the presented examples of automated interpretation of laboratory test results, selected possibilities of conducting numerical analyses with the use of MES have been demonstrated, which in their application are limited only by the imagination of experimenters (see numerical analyses based on the inclusion of soil microstructure, eg [22]).…”
Section: Examples Of Application Of Proposed Methodologymentioning
confidence: 99%
“…According to the results of Bahloul [8], it can be concluded that Plaxis software predicted the real consolidation settlement after comparing the settlement observed in the field with that obtained by using Plaxis program, therefore, the finite element simulation is performed by the Plaxis program; a numerical investigation was carried out by a soft soil model to represent the load settlement and time settlement behavior of footing. The soft soil model is a Cam-Clay model that is utilized especially to study the primary compression of normally consolidated clay, so based on finite element analysis by this model found in the Plaxis program, the trends of ground settlement can be depicted accurately [9].…”
Section: Validation Of Finite Element Programmentioning
confidence: 99%
“…Immediate settlement of a rigid raft foundation can be calculated by the equation reported by Ishibashi and Hazarika [9], as mentioned below, equation ( 1)…”
Section: Immediate Settlementmentioning
confidence: 99%
“…También, (Zuo et al, 2018) mencionan la descripción de la conversión del drenaje por consolidación a la base compuesta basada en la función de distribución Ascend Semi-cauchy de la teoría de las Matemáticas Fuzzy, presenta la expresión de tiempo del grado de consolidación, pues verifica la precisión computacional de la expresión mediante datos medidos y confirma asentamiento total de la precarga secundaria después de la comparación y el cálculo por este método curva e-lop, que considera la influencia histórica del esfuerzo del suelo es más preciso al calcular el total asentamiento de la precarga secundaria, este método puede lograr la precisión de cálculo del asentamiento la postconstrucción con la expresión de grado de consolidación mencionado anteriormente. (Jie et al, 2017) comentan en un proyecto de construcción de una isla artificial basado en la recuperación de tierra marina a gran escala, el asentamiento del suelo es clave para afectar la operación. El asentamiento del suelo se obtiene observando las cartas del microscopio electrónico de escaneo-SEM, escanea la superficie de las muestras tratadas con un enfoque de haz de electrones y genera varias señales a diferentes profundidades, algunas fotos SEM reflejan lo esencial de la microestructura que influyen en la deformación y esfuerzo del suelo., mediante la combinación de cálculo numércio de la teoría de consolidación unidimensional de Terzhaghi y bidimensional de Biot.…”
unclassified